Ionic crosslinking wide damping temperature range self-healing asphalt waterproof coiled material

By introducing a variety of modifiers and precise process control into the waterproof coil, a multi-layer composite structure is formed, which solves the shortcomings of existing waterproof coils in terms of damping performance and self-healing properties, and effectively takes into account waterproof performance and damping performance and self-healing properties.

CN119910980APending Publication Date: 2025-05-02QINGDAO ORIENTAL YUHONG BUILDING MATERIALS CO LTD

Patent Information

Application Number
CN202510284666.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing waterproof coils have shortcomings in damping performance and self-healing properties, and it is difficult to effectively take into account waterproofing performance, damping performance and self-healing properties.

Method used

An ionic crosslinked wide damping temperature domain self-healing asphalt waterproof coil is designed. By introducing a variety of modifiers, such as maleic anhydride modified styrene-butadiene-styrene thermoplastic elastomer (SBS-MAH), carboxylic nitrile rubber (XNBR), nitrile rubber (NBR) and ethylene vinyl acetate rubber (EVM), and through precise process control and layer-layer coating steps, a multi-layer composite structure is formed.

Benefits of technology

It significantly improves the waterproof performance, self-healing performance and damping performance of the waterproof coil, effectively solves the damping problem of the building, and achieves effective consideration of waterproof performance, damping and self-healing properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119910980A_ABST
    Figure CN119910980A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of waterproof coiled materials, and discloses an ionic crosslinking wide damping temperature range self-healing asphalt waterproof coiled material. The waterproof coiled material comprises an upper surface isolating layer, an upper surface modified asphalt coating material layer, an upper inner modified asphalt coating material layer, a tire base layer, a lower inner modified asphalt coating material layer, a lower surface modified asphalt coating material layer and a lower surface isolating layer which are sequentially arranged from top to bottom, the coating material raw materials of each modified asphalt coating material layer comprise the following components: an asphalt matrix, a maleic anhydride modified styrene-butadiene-styrene thermoplastic elastomer, carboxy nitrile rubber, nitrile rubber, ethylene vinyl acetate rubber, an auxiliary agent, rubber powder and an inorganic filler. By means of designing a coating material formula, a production process and the like of the waterproof coiled material, the waterproof performance, the self-healing performance and the damping performance of the waterproof coiled material are improved, the damping problem of a building is effectively solved, and the waterproof performance, the damping performance and the self-healing performance are effectively considered fundamentally.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of waterproofing coiled materials, and more specifically, relates to an ion-crosslinked wide-damping temperature range self-healing asphalt waterproofing coiled material. Background Art

[0002] With the rapid development of modern science and technology, various mechanical equipment, vehicles, crowd activities, etc. generate a lot of vibration and noise, which are always present in people's daily life and work. These vibrations and noises not only affect our physical health, but also affect the service life of equipment and instruments. People have found in their research that the use of damping materials is an effective way to control vibration and noise. Damping materials can absorb the vibration energy generated by mechanical vibration and irreversibly convert it into heat energy, reducing the vibration capacity transmitted to the human ear and the machine, thereby reducing the impact of harmful vibration and noise on the human ear and the machine. The strength of the damping effect can be characterized by the dynamic mechanical properties of the material, including the storage modulus and the loss factor. The larger the loss factor (tanδ≥0.3), the better the damping effect. The area where tanδ≥0.3 is called the effective damping temperature range.

[0003] At present, humans often use building dampers for shock absorption of buildings, but lack material damping upgrades. Since most damping materials are materials with asynchronous storage modulus and loss modulus, polymer materials have become the first choice for damping materials, and an extra layer of damping material increases the construction cost in disguise. Therefore, waterproof membranes that combine waterproof materials with damping materials are a good way to reduce construction costs and improve the life of buildings and the living environment of humans. Therefore, there is an urgent need to develop a waterproof membrane with excellent waterproof performance, high self-healing properties, and good damping performance. Summary of the invention

[0004] The purpose of the present invention is to address the deficiencies of the prior art and propose an ion-crosslinked wide damping temperature range self-healing asphalt waterproofing membrane. The present invention intends to improve the waterproofing performance, self-healing performance and damping performance of the waterproofing membrane by designing the coating material formula and production process of the waterproofing membrane, effectively solving the damping problem of the building, and fundamentally achieving an effective balance between waterproofing performance, damping and self-healing properties.

[0005] In order to achieve the above-mentioned object, the present invention provides an ion-crosslinked wide damping temperature range self-healing asphalt waterproofing membrane, the waterproofing membrane comprising an upper surface isolation layer, an upper surface modified asphalt coating layer, an upper inner modified asphalt coating layer, a tread base layer, a lower inner modified asphalt coating layer, a lower surface modified asphalt coating layer and a lower surface isolation layer arranged in sequence from top to bottom;

[0006] The coating raw materials of each modified asphalt coating layer include the following components: asphalt base, maleic anhydride modified styrene-butadiene-styrene thermoplastic elastomer (SBS-MAH), carboxylated nitrile rubber (XNBR), nitrile rubber (NBR), ethylene vinyl acetate rubber (EVM), additives, rubber powder and inorganic filler.

[0007] According to the present invention, preferably, the coating raw materials of the upper surface modified asphalt coating layer, the coating raw materials of the upper inner modified asphalt coating layer, the coating raw materials of the lower surface modified asphalt coating layer and the coating raw materials of the lower inner modified asphalt coating layer each independently include the following components in parts by weight: 30-50 parts of asphalt base, 5-10 parts of maleic anhydride modified styrene-butadiene-styrene thermoplastic elastomer, 5-10 parts of carboxylated nitrile rubber, 5-10 parts of nitrile rubber, 10-20 parts of ethylene vinyl acetate rubber, 1-5 parts of additives, 8-16 parts of rubber powder and 8-20 parts of inorganic filler.

[0008] According to the present invention, preferably, the amount of each component in the coating raw material of the upper surface modified asphalt coating layer, the amount of each component in the coating raw material of the upper inner modified asphalt coating layer, the amount of each component in the coating raw material of the lower surface modified asphalt coating layer and the amount of each component in the coating raw material of the lower inner modified asphalt coating layer are different from each other.

[0009] According to the present invention, preferably, the method for preparing the coating material of each modified asphalt coating material layer comprises:

[0010] Using part of the inorganic filler as an isolation component to blend and grind with maleic anhydride modified styrene-butadiene-styrene thermoplastic elastomer, carboxylated nitrile rubber, nitrile rubber and ethylene vinyl acetate rubber to obtain a particle size refined modifier blend;

[0011] The particle size refinement modifier blend is mixed and stirred evenly with the asphalt matrix to obtain a uniform dispersion system;

[0012] Heating and stirring the uniformly dispersed system to obtain a dissolved system;

[0013] The dissolving system is mixed with the auxiliary agent and the rubber powder, stirred and reacted to obtain a reaction system;

[0014] The reaction system and the inorganic filler are mixed and stirred evenly to obtain the coating material of each modified asphalt coating layer.

[0015] According to the present invention, preferably, the inorganic filler used as the separating component accounts for 15-25% of the total weight of the inorganic filler.

[0016] According to the present invention, preferably, the particle size of the particle size refinement modifier blend is 40-60 mesh.

[0017] In the present invention, NBR and XNBR need to be refined after being thinned through a twin-roll mill to reduce the grinding time.

[0018] According to the present invention, preferably, the temperature for mixing the particle size refining modifier blend with the asphalt matrix is ​​135-145° C., the stirring rate is 250-350 r / min, and the time is 4.5-5.5 min.

[0019] In the present invention, the uniformly dispersed system is a particle size-refined modifier blend uniformly dispersed in an asphalt matrix without the presence of adhesive lumps.

[0020] According to the present invention, preferably, the temperature for heating and stirring the uniformly dispersed system is 185-195° C., the stirring rate is 450-550 r / min, and the time is 115-125 min.

[0021] In the present invention, the dissolution system is a particle size refinement modifier blend completely dissolved in the asphalt matrix.

[0022] According to the present invention, preferably, the temperature for mixing, stirring and reacting the dissolving system with the auxiliary agent and the rubber powder is 190-200° C., the stirring rate is 250-350 r / min, and the time is 35-45 min.

[0023] According to the present invention, preferably, the temperature for mixing and stirring the reaction system and the inorganic filler is 180-190° C., and the stirring rate is 150-250 r / min.

[0024] According to the present invention, preferably, the total thickness of the waterproof coiled material is 3-5 mm, the thickness of the base layer is 1.0-1.2 mm, and the thickness of the upper surface isolation layer and the lower surface isolation layer are each independently 0.015-0.025 mm.

[0025] According to the present invention, preferably, the thickness of the upper surface modified asphalt coating layer, the upper inner modified asphalt coating layer, the lower inner modified asphalt coating layer and the lower surface modified asphalt coating layer each independently accounts for 20-30% of the total thickness of all modified asphalt coating layers.

[0026] In the present invention, the thickness of the applied coating layer can be accurately controlled by the spacing of the thickness control rollers.

[0027] According to the present invention, preferably, based on the total weight of the asphalt matrix, the asphalt matrix includes 20-30% of 70# petroleum asphalt, 20-30% of 90# petroleum asphalt and 40-60% of 200# petroleum asphalt.

[0028] According to the present invention, preferably, the maleic anhydride grafting amount of the maleic anhydride modified styrene-butadiene-styrene thermoplastic elastomer is greater than 1%, wherein the styrene content in the styrene-butadiene-styrene thermoplastic elastomer is greater than 30%.

[0029] According to the present invention, preferably, the carboxyl nitrile rubber is 1072CG, with a carboxyl content of 7%.

[0030] According to the present invention, preferably, the nitrile rubber is at least one of N220S, 230S, 240S and 250S of Japan JSR.

[0031] According to the present invention, preferably, the ethylene vinyl acetate rubber is at least one of EVM900, EVM800, EVM700, EVM600, EVM500, EVM450 and EVM400, preferably at least one of EVM900, EVM800 and EVM700.

[0032] According to the present invention, preferably, the auxiliary agent includes a silane coupling agent, a solubilizer, a release agent and an antioxidant, and the amounts of the silane coupling agent, the solubilizer, the release agent and the antioxidant are 8-12%, 8-12%, 35-45% and 35-45% of the total amount of the auxiliary agent, respectively.

[0033] In the present invention, the silane coupling agent can promote the blending of the inorganic phase and the organic phase in the coating material. The release agent can prevent the rubber powder from bonding and agglomerating.

[0034] According to the present invention, preferably, the solubilizer is at least one of stearic acid compounds, zinc compounds and alkylphenol polysulfide compounds. In the present invention, the solubilizer can destroy the polysulfide bonds of tire rubber powder, thereby destroying the cross-linked structure of the rubber powder and converting it into a linear structure, thereby reducing the viscosity of the coating and improving the bonding performance of the coating layer.

[0035] According to the present invention, preferably, the antioxidant (slowing down material aging) is an amine antioxidant and / or a phenolic antioxidant.

[0036] According to the present invention, preferably, the rubber powder is formed by blending and grinding tire rubber sidewall rubber and tire rubber tread rubber, the mesh size of the rubber powder is 60-80 mesh, and the mass ratio of the tire rubber sidewall rubber to the tire rubber tread rubber is (0.8-1.2):(0.8-1.2).

[0037] According to the present invention, preferably, based on the total weight of the inorganic filler, the inorganic filler comprises 15-20% montmorillonite, 15-20% stone powder and / or talc, 15-20% spodumene and / or fly ash, 15-20% fumed silica, 15-20% sepiolite and 15-20% furnace carbon black. In the present invention, the inorganic filler is used as a filler and a separator.

[0038] According to the present invention, preferably, the base layer is obtained by drying and pre-impregnating the waterproof coiled material base with a drying temperature of 185-195°C and a drying time of >10s. In the present invention, the waterproof coiled material base is preferably a polyester base.

[0039] In the present invention, the waterproof coiled material base is completely soaked in the pre-soaking oil, leaving no unsoaked areas.

[0040] In the present invention, the preparation method of the ion-crosslinked wide damping temperature range self-healing asphalt waterproof membrane comprises the following steps:

[0041] S1: applying the coating material of the upper inner modified asphalt coating layer to the upper side of the tread base layer to obtain the upper inner modified asphalt coating layer; applying the coating material of the lower inner modified asphalt coating layer to the lower side of the tread base layer to obtain the lower inner modified asphalt coating layer;

[0042] S2: applying the coating material of the upper surface modified asphalt coating layer to the upper side of the upper inner modified asphalt coating layer to obtain the upper surface modified asphalt coating layer; applying the coating material of the lower surface modified asphalt coating layer to the lower side of the lower inner modified asphalt coating layer to obtain the lower surface modified asphalt coating layer;

[0043] S3: Covering the upper surface isolation layer and the lower surface isolation layer on the upper surface modified asphalt coating layer and the lower surface modified asphalt coating layer respectively to obtain the ion-crosslinked wide damping temperature range self-healing asphalt waterproof membrane.

[0044] The beneficial effects of the technical solution of the present invention are as follows: the present invention intends to improve the waterproof performance, self-healing performance and damping performance of the waterproof coiled material by designing the coating material formula and production process of the waterproof coiled material, effectively solve the damping problem of the building, and fundamentally achieve the effective balance between waterproof performance, damping and self-healing. Specifically:

[0045] 1. The ion-crosslinked wide damping temperature range self-healing asphalt waterproof membrane of the present invention adopts a multi-layer composite structure, which comprehensively considers multiple factors such as waterproof performance, self-healing performance, damping performance, material cost, etc., and overcomes the limitation that it is difficult to consider all aspects of performance with a single main material.

[0046] 2. The NBR (nitrile rubber) and EVM (ethylene vinyl acetate rubber) introduced in the present invention have a wide damping temperature range. The comprehensive performance of the material is improved by modifying the asphalt. By applying in batches, the coating layers of different formula materials are distributed in parallel on the upper and lower surfaces of the tire base layer in turn. On the basis of chemically changing its damping properties, the vibration wave is physically converted into heat energy during the propagation process, which can effectively improve the damping performance of the material. The present invention ensures the uniformity of the waterproof coiled material through precise process control and the coating steps of layers of coating materials with different formula materials, and also has different damping factors in the vertical and horizontal directions of the coiled material, thereby making the damping performance of the waterproof coiled material more excellent.

[0047] 3. The polar functional groups of SBS-MAH (maleic anhydride modified styrene-butadiene-styrene thermoplastic elastomer) and XNBR (carboxylated nitrile rubber) introduced in the present invention can form ionic cross-linking bonds with zinc ions (provided by zinc-based ionic compounds) in rubber powder and additives, so that the materials have higher tensile strength and tear strength at room temperature. At high temperatures, the ionic bonds will be destroyed and rearranged, so that after the materials are destroyed, the coil coating layer can be repaired under the action of ionic bonds.

[0048] 4. The present invention not only solves the problem that traditional waterproofing membranes do not have damping properties, but also gives waterproofing membranes self-healing properties, improves the strength of the modified asphalt coating layer, and provides strong support for the multifunctionalization of waterproofing membranes. This innovation has positive significance for promoting the multifunctionalization of waterproofing membranes in the construction industry and improving the service life of waterproofing membranes.

[0049] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] The above and other objects, features and advantages of the present invention will become more apparent through a more detailed description of exemplary embodiments of the present invention with reference to the accompanying drawings.

[0051] Figure 1 The dynamic mechanical property loss factor (tan δ ≥ 0.3) characterization of the waterproof membranes of Examples 1-2 of the present invention and Comparative Example 1 is shown. DETAILED DESCRIPTION

[0052] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.

[0053] In the following embodiments and comparative examples:

[0054] The maleic anhydride modified styrene-butadiene-styrene thermoplastic elastomer (SBS-MAH) is from Dongguan Jingke Polymer Co., Ltd. (toughened, compatible, impact-resistant, high-grafting rate thermoplastic elastomer modifier maleic anhydride grafted SBS-G-MAH, standard 1.0%, measured 1.03%, wherein the styrene content in the styrene-butadiene-styrene thermoplastic elastomer is measured to be 36%);

[0055] SBS was purchased from SBS Sinopec Baling YH-813;

[0056] The carboxylated nitrile rubber (XNBR) is Nandi carboxylated nitrile XNBR rubber 1072CG, Nandi Chemical Industry Co., Ltd., with a carboxyl content of 7%;

[0057] Nitrile rubber (NBR) is N220S from Japan JSR;

[0058] The ethylene vinyl acetate rubber (EVM) is EVM900;

[0059] The rubber powder is formed by mixing and grinding tire rubber sidewall rubber and tire rubber tread rubber, the mesh number of the rubber powder is 60-80 meshes, and the mass ratio of the tire rubber sidewall rubber to the tire rubber tread rubber is 1:1;

[0060] Based on the total weight of the inorganic filler, the inorganic filler ratio includes 15% montmorillonite, 20% talc, 15% fly ash, 20% fumed silica, 15% sepiolite and 15% furnace carbon black;

[0061] The auxiliary agent ratio includes 10% silane coupling agent, 10% solubilizer, 40% isolation agent and 40% antioxidant, wherein: the silane coupling agent is γ-aminopropyl triethoxysilane (silane coupling agent KH-550, Hangzhou Jessica Chemical Co., Ltd.); the isolation agent is 600 mesh talcum powder (Qingdao Dongyufeng New Building Materials Manufacturing Co., Ltd.); the antioxidant is 4010NA (N-isopropyl-N'-phenyl-p-phenylenediamine, antioxidant 4010NA is a light red to purple-red, brown granular, the molecular formula is C 15 H 18 N2); the solubilizer is a mixture of poly (p-tert-butylphenol disulfide) and zinc stearate (zinc stearate) in a mass ratio of 1:1.

[0062] Example 1

[0063] The present embodiment provides an ion-cross-linked wide damping temperature range self-healing asphalt waterproof membrane, which includes an upper surface isolation layer, an upper surface modified asphalt coating layer, an upper inner modified asphalt coating layer, a tread base layer, a lower inner modified asphalt coating layer, a lower surface modified asphalt coating layer and a lower surface isolation layer, which are arranged in sequence from top to bottom.

[0064] The coating materials of each modified asphalt coating layer include the following components: asphalt base (70# petroleum asphalt, 90# petroleum asphalt and 200# petroleum asphalt), maleic anhydride modified styrene-butadiene-styrene thermoplastic elastomer (SBS-MAH), carboxylated nitrile rubber (XNBR), nitrile rubber (NBR), ethylene vinyl acetate rubber (EVM), additives, rubber powder and inorganic filler;

[0065] The amounts of each component in the coating material raw material of the modified asphalt coating layer in the upper table, the amounts of each component in the coating material raw material of the upper inner modified asphalt coating layer, the amounts of each component in the coating material raw material of the modified asphalt coating layer in the lower table, and the amounts of each component in the coating material raw material of the lower inner modified asphalt coating layer are exactly the same, as shown in Table 1;

[0066] Table 1

[0067]

[0068]

[0069] The preparation method of the coating material of each modified asphalt coating material layer includes:

[0070] Using part of the inorganic filler (accounting for 20% of the total weight of the inorganic filler) as an isolation component, blending and grinding with maleic anhydride modified styrene-butadiene-styrene thermoplastic elastomer, carboxyl nitrile rubber, nitrile rubber and ethylene vinyl acetate rubber (NBR and XNBR need to be refined after being thinned through a double-roll mill to reduce the grinding time) to obtain a particle size refined modifier blend (0% for particles above 40 mesh, 94% for particles between 40 and 60 mesh, and 6% for particles below 60 mesh);

[0071] Add the particle size refinement modifier blend and the asphalt matrix into a reactor equipped with a temperature control device and a stirring device, mix and stir evenly, control the temperature to 140±5°C, and stir at a rate of 300r / min. After stirring and dispersing for 5 minutes, the particle size refinement modifier blend is evenly dispersed in the asphalt matrix without any sticky block objects, and a uniform dispersion system is obtained;

[0072] Subsequently, the reaction temperature was raised to 190°C, the stirring rate was 500 r / min, and the physical reaction was carried out for 120 minutes until the particle size refinement modifier blend was completely dissolved in the asphalt matrix to obtain a dissolved system;

[0073] The temperature was controlled at 195° C. and the stirring rate was 300 r / min, and the dissolved system was mixed with the auxiliary agent and the rubber powder and stirred and reacted for 40 minutes to obtain a reaction system;

[0074] The temperature was controlled at 185° C. and the stirring rate was 200 r / min. The reaction system and the inorganic filler were mixed, stirred and dispersed uniformly to obtain the coating material of each modified asphalt coating layer.

[0075] The base layer is obtained by drying the base of the waterproof coiled material and pre-impregnating it with pre-impregnation oil. The drying temperature is 185-195° C. and the drying time is greater than 10 seconds.

[0076] The total thickness of the waterproof membrane is 3-5mm, the thickness of the tread base layer is 1.0-1.2mm, the thickness of the upper surface isolation layer and the lower surface isolation layer are each independently 0.02mm; the thickness of the upper modified asphalt coating layer, the upper inner modified asphalt coating layer, the lower inner modified asphalt coating layer and the lower surface modified asphalt coating layer each independently accounts for 25% of the total thickness of all modified asphalt coating layers.

[0077] The preparation method of the ion-crosslinked wide damping temperature range self-healing asphalt waterproof membrane of this embodiment comprises the following steps:

[0078] S1: applying the coating material of the upper inner modified asphalt coating layer to the upper side of the tread base layer to obtain the upper inner modified asphalt coating layer; applying the coating material of the lower inner modified asphalt coating layer to the lower side of the tread base layer to obtain the lower inner modified asphalt coating layer;

[0079] S2: applying the coating material of the upper surface modified asphalt coating layer to the upper side of the upper inner modified asphalt coating layer to obtain the upper surface modified asphalt coating layer; applying the coating material of the lower surface modified asphalt coating layer to the lower side of the lower inner modified asphalt coating layer to obtain the lower surface modified asphalt coating layer;

[0080] S3: Covering the upper surface isolation layer and the lower surface isolation layer on the upper surface modified asphalt coating layer and the lower surface modified asphalt coating layer respectively, and obtaining the ion-crosslinked wide damping temperature range self-healing asphalt waterproofing membrane through cooling, rolling and packaging.

[0081] Example 2

[0082] The difference between this embodiment and embodiment 1 is only that:

[0083] The amounts of the various components in the coating raw materials of the modified asphalt coating layer in the upper table are shown in 3# in Table 1, the amounts of the various components in the coating raw materials of the upper inner modified asphalt coating layer are shown in 1# in Table 1, the amounts of the various components in the coating raw materials of the modified asphalt coating layer in the lower table are shown in 4# in Table 1, and the amounts of the various components in the coating raw materials of the lower inner modified asphalt coating layer are shown in 2# in Table 1.

[0084] Comparative Example 1

[0085] The difference between this comparative example and Example 1 is only that:

[0086] The preparation method of the coating material of each modified asphalt coating material layer includes:

[0087] Adding SBS and asphalt matrix into a reaction kettle equipped with a temperature control device and a stirring device and mixing and stirring uniformly to obtain SBS modified asphalt;

[0088] The temperature was controlled at 195° C. and the stirring rate was 300 r / min, and the SBS modified asphalt was mixed with the additive and the rubber powder and stirred and reacted for 40 minutes to obtain a reaction system;

[0089] The temperature was controlled at 185° C. and the stirring rate was 200 r / min. The reaction system and the inorganic filler were mixed, stirred and dispersed uniformly to obtain the coating material of each modified asphalt coating layer.

[0090] The present invention characterizes the dynamic mechanical property loss factor (tan δ ≥ 0.3) of the waterproof membranes of the above-mentioned embodiments and comparative examples. The results are as follows: Figure 1 As shown. Figure 1 It can be seen that:

[0091] The coating material formula value of Example 1 is the average value of the four coating material formulas in Example 2. The optimized production method of Example 1 of the present invention is compared with the traditional production method of Comparative Example 1. The optimized method introduces a variety of modifiers (SBS-MAH, NBR, XNBR, EVM) to prepare modified asphalt, giving the waterproof coiled material an ion cross-linked network with higher strength and self-healing properties. By adding four modifiers (SBS-MAH, NBR, XNBR, EVM), the damping temperature range of the material is further broadened to 55°C.

[0092] Example 2 prepares coating materials with different formula systems based on Example 1 and applies them in batches. This production process ensures the uniformity of the waterproof membrane through precise process control and layer-by-layer coating steps, and also makes the membrane have different damping factors in the vertical and horizontal directions. On the basis of chemically changing its damping properties, the vibration wave is physically converted into heat energy during propagation, and its damping performance is more excellent.

[0093] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. An ion-crosslinked wide damping temperature range self-healing asphalt waterproofing membrane, characterized in that: The waterproofing coiled material comprises an upper surface isolation layer, an upper surface modified asphalt coating layer, an upper inner modified asphalt coating layer, a tread base layer, a lower inner modified asphalt coating layer, a lower surface modified asphalt coating layer and a lower surface isolation layer, which are arranged in sequence from top to bottom; The coating material raw materials of each modified asphalt coating layer include the following components: asphalt matrix, maleic anhydride modified styrene-butadiene-styrene thermoplastic elastomer, carboxylated nitrile rubber, nitrile rubber, ethylene vinyl acetate rubber, additives, rubber powder and inorganic filler.

2. The ion-crosslinked wide damping temperature range self-healing asphalt waterproofing membrane according to claim 1, wherein: The coating raw materials of the upper surface modified asphalt coating layer, the coating raw materials of the upper inner modified asphalt coating layer, the coating raw materials of the lower surface modified asphalt coating layer and the coating raw materials of the lower inner modified asphalt coating layer each independently include the following components in parts by weight: 30-50 parts of asphalt base, 5-10 parts of maleic anhydride modified styrene-butadiene-styrene thermoplastic elastomer, 5-10 parts of carboxylated nitrile rubber, 5-10 parts of nitrile rubber, 10-20 parts of ethylene vinyl acetate rubber, 1-5 parts of additives, 10-15 parts of rubber powder and 10-12.5 parts of inorganic filler.

3. The ion-crosslinked wide damping temperature range self-healing asphalt waterproofing membrane according to claim 1 or 2, wherein: The amounts of each component in the coating raw materials of the upper surface modified asphalt coating layer, the amounts of each component in the coating raw materials of the upper inner modified asphalt coating layer, the amounts of each component in the coating raw materials of the lower surface modified asphalt coating layer, and the amounts of each component in the coating raw materials of the lower inner modified asphalt coating layer are different from each other.

4. The ion-crosslinked wide damping temperature range self-healing asphalt waterproofing membrane according to claim 1, wherein: The preparation method of the coating material of each modified asphalt coating material layer includes: Using part of the inorganic filler as an isolation component to blend and grind with maleic anhydride modified styrene-butadiene-styrene thermoplastic elastomer, carboxylated nitrile rubber, nitrile rubber and ethylene vinyl acetate rubber to obtain a particle size refined modifier blend; The particle size refinement modifier blend is mixed and stirred evenly with the asphalt matrix to obtain a uniform dispersion system; Heating and stirring the uniformly dispersed system to obtain a dissolved system; The dissolving system is mixed with the auxiliary agent and the rubber powder, stirred and reacted to obtain a reaction system; The reaction system and the inorganic filler are mixed and stirred evenly to obtain the coating material of each modified asphalt coating layer.

5. The ion-crosslinked wide damping temperature range self-healing asphalt waterproofing membrane according to claim 4, wherein: The inorganic filler used as the isolation component accounts for 15-25% of the total weight of the inorganic filler; The particle size of the particle size refinement modifier blend is 40-60 mesh; The temperature of mixing the particle size refinement modifier blend with the asphalt matrix is ​​135-145°C, the stirring rate is 250-350r / min, and the time is 4.5-5.5min; The temperature of heating and stirring the uniformly dispersed system is 185-195° C., the stirring rate is 450-550 r / min, and the time is 115-125 min; The temperature for mixing the dissolving system with the additive and the rubber powder and stirring and reacting is 190-200°C, the stirring rate is 250-350r / min, and the time is 35-45min; The reaction system and the inorganic filler are mixed and stirred at a temperature of 180-190° C. and a stirring rate of 150-250 r / min.

6. The ion-crosslinked wide damping temperature range self-healing asphalt waterproofing membrane according to claim 1, wherein: The total thickness of the waterproof coiled material is 3-5 mm, the thickness of the base layer is 1.0-1.2 mm, and the thickness of the upper surface isolation layer and the lower surface isolation layer are each independently 0.015-0.025 mm.

7. The ion-crosslinked wide damping temperature range self-healing asphalt waterproofing membrane according to claim 6, wherein: The thickness of the upper surface modified asphalt coating layer, the upper inner modified asphalt coating layer, the lower inner modified asphalt coating layer and the lower surface modified asphalt coating layer independently accounts for 20-30% of the total thickness of all modified asphalt coating layers.

8. The ion-crosslinked wide damping temperature range self-healing asphalt waterproofing membrane according to claim 1, wherein: Based on the total weight of the asphalt matrix, the asphalt matrix includes 20-30% of 70# petroleum asphalt, 20-30% of 90# petroleum asphalt and 40-60% of 200# petroleum asphalt; The maleic anhydride grafting amount of the maleic anhydride modified styrene-butadiene-styrene thermoplastic elastomer is greater than 1%, wherein the styrene content in the styrene-butadiene-styrene thermoplastic elastomer is greater than 30%; The carboxyl nitrile rubber is 1072CG, with a carboxyl content of 7%; The nitrile rubber is at least one of N220S, 230S, 240S and 250S of Japan JSR; The ethylene vinyl acetate rubber is at least one of EVM900, EVM800, EVM700, EVM600, EVM500, EVM450 and EVM400, preferably at least one of EVM900, EVM800 and EVM700; The auxiliary agent includes a silane coupling agent, a solubilizing agent, a release agent and an antioxidant, and the dosage of the silane coupling agent, the solubilizing agent, the release agent and the antioxidant is 8-12%, 8-12%, 35-45% and 35-45% of the total amount of the auxiliary agent respectively; The rubber powder is formed by blending and grinding tire rubber sidewall rubber and tire rubber tread rubber, the mesh number of the rubber powder is 60-80 meshes, and the mass ratio of the tire rubber sidewall rubber to the tire rubber tread rubber is (0.8-1.2): (0.8-1.2); Based on the total weight of the inorganic filler, the inorganic filler comprises 15-20% montmorillonite, 15-20% stone powder and / or talc, 15-20% spodumene and / or fly ash, 15-20% fumed silica, 15-20% sepiolite and 15-20% furnace carbon black.

9. The ion-crosslinked wide damping temperature range self-healing asphalt waterproofing membrane according to claim 8, wherein: The solubilizer is at least one of a stearic acid compound, a zinc compound and an alkylphenol polysulfide compound; The antioxidant is an amine antioxidant and / or a phenol antioxidant.

10. The ion-crosslinked wide damping temperature range self-healing asphalt waterproofing membrane according to claim 1, wherein: The base layer is obtained by drying the base of the waterproof coiled material and pre-impregnating it with pre-impregnation oil. The drying temperature is 185-195° C. and the drying time is greater than 10 seconds.

Citation Information

Patent Citations

  • Multilayer constrained-layer damping

    CN112135730A

  • Hard SBS modified asphalt waterproof coiled material and preparation process thereof

    CN116872583A

  • Carboxylated rubber composite material and preparation method thereof

    CN117487260A

Cited By

  • Self-adhesive asphalt waterproof coiled material as well as preparation method and application thereof

    CN122278369A

  • Self-adhesive bituminous waterproofing membrane, method for its production and use

    CN122278369B